Kanser ve Enfeksiyon - Alyıldız, Neşe; Alan, Murat; Güçlü Kantar, Taliha; Teksöz, Duygu; Aydın, Asım Armağan; Öner, İrem; Ellez, Halil İbrahim; Türkel, Recep; Biter, Sedat; Buğday, İrfan; Çakan Demirel, Burçin; Gökçek, Savaş; et al. (2023)
-